Perbandingan Tebal dan Analisis Kerusakan Perkerasan Lentur Menggunakan Program KENPAVE dan Metode Asphalt Institute - Setiawan M, Dian; Rahmawati, Anita; Setiawan, Iwan Bagus (Semesta Teknika, 2018)
The mechanistic-empirical method is one of the techniques used in the design of pavement thickness. Maospati-Sukomoro Road is the primary access to Magetan City which is traversed by heavy vehicle traffic. This research was conducted with the objective to design the pavement thickness and to analyse the pavement performance against fatigue cracking and rutting. Bina Marga 1987 and AASHTO 1993 were used as the empirical method in this research. The results then investigated with KENPAVE program as the mechanistic method. The calculations showed that the Bina Marga 1987 produce Nd value of 7,52x105 and Nf value of 5,77x1012 whereas the AASHTO 1993 produce Nd value of 2,12x109 and Nf value of 1,42x1011. The result indicated that the designed pavement thickness based on the Bina Marga 1987 method is unable to serve the planned traffic load and will be damaged if there is no immediate maintenance work. In another side, the designed pavement thickness based on the AASHTO 1993 method is capable of serving the planned traffic load.